17 Improving Frailty Identification and Comprehensive Geriatric Assessment (CGA) Completion on the Wards. (6th February 2020) - Verma, D; Bonora, F; Walker, R; Kaneshamoorthy, M; Bafadhel, L
Abstract: Introduction: The Comprehensive Geriatric Assessment (CGA) is known to deliver substantial and measurable health improvements to frail older people, including increased independence and a reduction in mortality. 1 The Clinical Frailty Scale (CFS) can detect older adults at higher risk of complicated course and longer hospital stay. 2 Despite the known benefits, previous audits has shown poor documentation on geriatric wards at Southend Hospital. Therefore, we devised a Quality Improvement Project to improve the uptake of both these. Methods: A total of two Plan Do Study Act (PDSA) cycles were completed where CGA completion and CFS documentation was audited. Each cycle lasted two weeks (25 patients). Qualitative feedback was obtained from the members of multidisciplinary team to aid improvements. The baseline audit was based on the introduction of a 2-page ward proforma for all new patients. The first intervention was an improved 2-page ward-proforma. The second intervention was a single page ward-proforma. Results: Originally, 40% of new patients admitted onto the ward had a CGA assessment and CFS score. After the first intervention, 79% (19) patients had a CFS score and a CGA assessment. 21% had a full CGA completed and 58% had partial CGA. Feedback included wanting a single page proforma to increase uptake. Questions needed to be more unambiguous and more tick boxes. After the second intervention 100% (25) patients had a CFS score and a CGA assessment. 40% (10) had a full CGA completed and 60% (15) had a partial CGA. Feedback include incorporating the ward round documentation to avoid repetition. Conclusions: The results show that by using a focused, concise and user-friendly proforma, uptake of the Comprehensive Geriatric Assessment and Clinical Frailty Scale can be significantly increased, bringing substantial and measurable health improvements to frail older people admitted to elderly care wards. References: 1. Welsh TJ, Gordon AL, Gladman JR. Int J Clin Pract. 2014;68(3):290–293. 2. Juma S, Taabazuing MM, Montero-Odasso M. Can Geriatr J. 2016;19(2):34–39.